2011
DOI: 10.1007/s00213-011-2250-3
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco withdrawal components and their relations with cessation success

Abstract: Rationale Tobacco withdrawal is a key factor in smoking relapse, but important questions about the withdrawal phenomenon remain. Objectives This research was intended to provide information about two core components of withdrawal (negative affect and craving): 1) how various withdrawal symptom profile dimensions (e.g., mean level, volatility, extreme values) differ between negative affect and craving; and 2) how these dimensions relate to cessation outcome. Methods Adult smokers (N=1504) in a double-blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
95
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 42 publications
18
95
0
1
Order By: Relevance
“…Smokers frequently report intense craving even without nicotine deprivation (Hughes, 1992), and many endorse more severe urges than during abstinence (Cox et al, 2001;Piper et al, 2011). In this regard, clonidine has shown to reduce craving following smoking cessation and it seems less effective in attenuating smoking-induced craving (Knott et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Smokers frequently report intense craving even without nicotine deprivation (Hughes, 1992), and many endorse more severe urges than during abstinence (Cox et al, 2001;Piper et al, 2011). In this regard, clonidine has shown to reduce craving following smoking cessation and it seems less effective in attenuating smoking-induced craving (Knott et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Given that these enthusiastic users of e-cigarettes still considered their product inferior to cigarettes in these areas suggests that they may be at risk of smoking relapse. In particular, affect regulation may be a prepotent motivator of tobacco use 60,61 , whereas weight gain has been cited as a primary reason for putting off quit attempts, especially in women. [62][63][64] Thus, these expectancies may represent targets for relapse-prevention efforts directed at e-cigarette users, as may be the development of relevant coping skills to prevent cigarette smoking relapse.…”
Section: E-cigarettes Versus Cigarettesmentioning
confidence: 99%
“…First, we examine withdrawal and baseline dependence to understand the processes involved in smoking after a quit attempt. Prior research has demonstrated that withdrawal is a key factor involved in lapse and relapse (Javitz, Brigham, Lessov-Schlaggar, Krasnow, & Swan, 2009;Piasecki, Jorenby, Smith, Fiore, & Baker, 2003;Piper et al, 2011). Two primary withdrawal factors have been identified, which are strongly related to relapse or later smoking status: smoking urges and negative affect (Piasecki et al, 2000;Piper et al, 2011;Zhou et al, 2009).…”
Section: Motivating Example: Predictors Of Smoking After Quit Attemptmentioning
confidence: 99%
“…Prior research has demonstrated that withdrawal is a key factor involved in lapse and relapse (Javitz, Brigham, Lessov-Schlaggar, Krasnow, & Swan, 2009;Piasecki, Jorenby, Smith, Fiore, & Baker, 2003;Piper et al, 2011). Two primary withdrawal factors have been identified, which are strongly related to relapse or later smoking status: smoking urges and negative affect (Piasecki et al, 2000;Piper et al, 2011;Zhou et al, 2009). In addition to predicting longer term relapse, increases in smoking urges or cravings and negative affect are associated with immediate smoking lapses (Berkman et al, 2011;Shiffman & Waters, 2004).…”
Section: Motivating Example: Predictors Of Smoking After Quit Attemptmentioning
confidence: 99%
See 1 more Smart Citation